Multifamily building with three levels of ferrocement - Pérez Garezález, Ernesto (2019)
The work is concibed for the necessity of studying new materials that allow to buildresistant housings of up to three levels, worthy, sure, economic and sustainable. As theferrocement, a mortar highly reinforced with metallic mesh, offers wide possibilitiesin the execution of these premises. It leaves of previous works carried out in Cuba bythe authors and realize the study, keeping in mind the growing demand of housingsof low cost and the shortage of offers in this sense. In this is carried out the structuralmodelation keeping in mind the physical-mechanical characteristics of the ferrocementand the other materials that intervene in a building of housings of 3 plants withwalls and floor of nervouspanels of ferrocement of 3 cm of thickness as well as theseismic load corresponding to Cuba. The modelation includes the discretization ofthe structure in finite elements, what facilitates an integral study of the elements ofsupports and closings, as well as the evaluation of the connections among them, lateris carried out the design of the ferrocement panels being proven substantial savingsof materials with relationship to the traditional housings. This constitutes the startingpoint for the development of detailed executive projects and tipologys of housings isstudied that will generate the future development of constructive systems